If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(5x + -4) + 4(18 + -5x) + -3(3x + 4) = -7 Reorder the terms: 6(-4 + 5x) + 4(18 + -5x) + -3(3x + 4) = -7 (-4 * 6 + 5x * 6) + 4(18 + -5x) + -3(3x + 4) = -7 (-24 + 30x) + 4(18 + -5x) + -3(3x + 4) = -7 -24 + 30x + (18 * 4 + -5x * 4) + -3(3x + 4) = -7 -24 + 30x + (72 + -20x) + -3(3x + 4) = -7 Reorder the terms: -24 + 30x + 72 + -20x + -3(4 + 3x) = -7 -24 + 30x + 72 + -20x + (4 * -3 + 3x * -3) = -7 -24 + 30x + 72 + -20x + (-12 + -9x) = -7 Reorder the terms: -24 + 72 + -12 + 30x + -20x + -9x = -7 Combine like terms: -24 + 72 = 48 48 + -12 + 30x + -20x + -9x = -7 Combine like terms: 48 + -12 = 36 36 + 30x + -20x + -9x = -7 Combine like terms: 30x + -20x = 10x 36 + 10x + -9x = -7 Combine like terms: 10x + -9x = 1x 36 + 1x = -7 Solving 36 + 1x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 1x = -7 + -36 Combine like terms: 36 + -36 = 0 0 + 1x = -7 + -36 1x = -7 + -36 Combine like terms: -7 + -36 = -43 1x = -43 Divide each side by '1'. x = -43 Simplifying x = -43
| 5(5c-1)-1=23c+8 | | 8x^2+84x-44=0 | | 9+9(-3)= | | -2(2b+1)+(5b-2)=0 | | x=5x^2-2x-4 | | x-3x=6x-5-8x | | 0.4(5x-15)=4 | | (7+1.5y)+(2x-14)=25 | | (5y+5)-(4+4y)=4 | | 20+16= | | 6n=186 | | -20=4x | | (4x+6)(3x-7)= | | p^2+2p-360=0 | | 8(7n-2)=-16+n | | -20+16= | | 9(x+8)+12=8(8x+8)+10 | | 10(x+3)=10(x+3) | | 2x+2(x-4)=112 | | 3t+1+5t-7t=2+6 | | y=5x^2-2x-4 | | 2x^9-16x^7= | | 4(-4t^2+16t-7)=0 | | 0.7(6x+2)=1.1-(x+6)2x | | 8x-7y=5 | | x+6+x+3+3x-3+x^2-2x=46 | | 2v+40=8(5+v) | | 7.5x+2=6.5x | | p+p+30+p(4)-32=868 | | 12-20+125= | | 2(7x-5)= | | 18x-5=18x-6 |